Encapsulation of greenhouse gases in clathrate hydrates with insights into structure, energetics, chemical interactions, and environmental implications - Arun Ramamurthy; Giridhar Baburao; Abburi Jahnavi; Gopi Ragupathy (Scientific Reports)
Abstract The encapsulation of greenhouse gases (GHGs), such as CCl $$_4$$ , CF $$_2$$ Cl $$_2$$ , CH $$_3$$ Br, CH $$_3$$ Cl, CH $$_4$$ , CO, CO $$_2$$ , H $$_2$$ S, CH $$_3$$ F, N $$_2$$ O, NF $$_3$$ , O $$_3$$ , CF $$_4$$ , SF $$_6$$ , and SO $$_2$$ , within 5 $$^{12}$$ , 5 $$^{12}$$ 6 $$^2$$ , and 5 $$^{12}$$ 6 $$^4$$ clathrate hydrate cages is being investigated in our study using Density Functional Theory (DFT). The smaller cages introduce steric constraints, leading to bond distortions and significant vibrational blue-shifts, while larger cages offer greater flexibility, resulting in red-shifts or minimal vibrational alterations. Intermediate-sized cages provide a nuanced balance between spatial limitations and structural stabilization. In the $$5^{12}$$ cage, fewer guests exhibit red-shifts, whereas the larger $$5^{12}6^2$$ and $$5^{12}6^4$$ cages show more frequent red-shifts due to enhanced host–guest interactions. Natural Bonding Orbital (NBO) analysis reveals systematic changes in orbital contributions, occupancies, and anti-bonding interactions upon encapsulation, highlighting enhanced bond stabilization and a reduction in environmental reactivity. Atoms in Molecules (AIM) analysis further corroborates that encapsulated molecules exhibit strong bonding, remaining securely trapped and exhibiting minimal reactivity. Energy Decomposition Analysis (EDA) indicates that while smaller cages amplify interaction energies, they can also introduce substantial steric strain. In contrast, Non-Covalent Interaction (NCI) analysis highlights that the stability of hydrate cages is enhanced by stronger H-bonds and weaker van der Waals interactions as cage size increases. This underscores the potential of clathrate hydrates for encapsulating GHGs.